The belief that secondhand smoke causes serious illness among Chinese smokers: Smoking cessation and intention to quit - Madewell, Zachary Joseph (Tob Prev Cessat, 2018)
INTRODUCTION: Approximately 70% of Chinese adults are exposed to secondhand smoke (SHS) each week and 100 000 people die from SHS every year in China. This study evaluates associations between the belief that SHS causes serious illness and intention to quit, attempts to quit, and quitting smoking, among Chinese adult smokers. METHODS: A nationally representative sample of 4866 current and former adult smokers in the Global Adult Tobacco Survey was used for analysis. Multivariable weighted regression models were built to determine significant associations between smoking cessation behavior and the belief that SHS causes serious illness. RESULTS: The belief that SHS causes serious illness was associated with intention to quit (AOR 1.62, 95% CI: 1.24, 2.12) and quitting smoking (AOR 1.44, 95% CI: 1.15, 1.81). Other variables associated with smoking cessation behavior included not permitting smoking at home (intending: AOR 1.59, 95% CI: 1.10, 2.31; attempting: AOR 1.73, 95% CI: 1.25, 2.40; quitting: AOR 2.71, 95% CI: 1.90, 3.89) and the belief that smoking causes serious illness (attempting: AOR 1.63, 95% CI: 1.14, 2.33; quitting: AOR 1.66, 95% CI: 1.21, 2.28). CONCLUSIONS: These results indicate that believing SHS causes serious illness may play a role in quitting smoking. In China’s collectivistic culture, interventions should focus on how SHS exposure affects the health of friends and family. This message can be combined with other proven tobacco control methods such as: smoking bans in public places, warning labels on cigarette packages, high cigarette taxes, and mass media campaigns to reduce tobacco use.